2012
DOI: 10.1002/biot.201200220
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin removal and prevention for pre‐clinical biologics production

Abstract: The removal of endotoxin from protein solutions and its prevention are key to the success of recombinant protein production due to the possible pyogenic response in mammals caused by contaminated samples. In the pre-clinical situation, protein production is often carried out in a non-good manufacturing practice (GMP) setting, utilizing bacterial DNA for transient transfection and non-validated cleaning techniques. Here, we present our findings evaluating various options for endotoxin removal, and propose strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Previous studies have shown that endotoxin elutes with protein aggregates in gel filtration chromatography; however, it was unknown if endotoxin was directly associated with the aggregates or was simply eluting at the same time, based on size. Endotoxin monomers are composed of a polysaccharide region and a lipid region, and are well known to form supramolecular aggregates in aqueous solutions because of their amphipathic structures .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that endotoxin elutes with protein aggregates in gel filtration chromatography; however, it was unknown if endotoxin was directly associated with the aggregates or was simply eluting at the same time, based on size. Endotoxin monomers are composed of a polysaccharide region and a lipid region, and are well known to form supramolecular aggregates in aqueous solutions because of their amphipathic structures .…”
Section: Resultsmentioning
confidence: 99%
“…Although the final preparation still contained detectable endotoxin levels, the amounts were close to Good Manufacturing Practice standards. Given that endotoxin limits for protein-based injectables are typically 0.5 EU/mg, an additional endotoxin removal step(s) [32] may be required for use of recombinant apoA-I isolated by the present protocol in humans. Regardless, overall low endotoxin content together with scalability of the two-step process combines to makes this purification scheme an attractive option to produce WT apoA-I for commercial and pharmaceutical applications.…”
Section: Discussionmentioning
confidence: 99%
“…However, common sterilization procedures are usually not efficient in removing endotoxin contamination in NP samples. Techniques developed to remove endotoxin from samples are usually called ‘depyrogenation’ techniques [40,49]. …”
Section: General Aspects Of Dds Toxicologymentioning
confidence: 99%